MANAJEMEN SIRKULASI STOK ATK PADA PT.ANGKASA PURA I BANJARMASIN MEMANFAATKAN SISTEM INFORMASI - Erna Herliani; Yeffriansjah Salim (Nusantara Hasana Journal, 2021)
PT. Angkasa Pura I (Persero) Syamsuddin Noor Airport, is located in Syamsudin Noor Village, Landasan Ulin District, Banjarbaru City, South Kalimantan. PT. Angkasa Pura I Banjarmasin has very dense office administration activities, circulation or the use of office stationery which is routinely used every day at all levels of management of PT. Angkasa Pura I Banjarmasin. Calculation of stock taking is done once every 1 month. Employees who handle the circulation of the use of office stationery still use the Microsoft Excel application every month. The problem felt by the employees who manage the circulation of office stationery is the difficulty in calculating the stock of office stationery considering the large number and variety of office stationery items ranging from pens, pencils, rulers, paper, to ink equipment and printer cartridges that are used up. Difficulty making reports on the use of stock cards for office stationery items that are used every month and takes a long time to make reports, human calculation errors in recording inventory. The information system created records the income of stationery supplied from the Jakarta head office and records work units requesting the use of stationery so that the remaining available office stationery is monitored easily and quickly. The system makes reports on ATK income and circulation of office stationery usage every month quickly and accompanied by correct and accurate data.